Parsaclisib, a PI3Kδ inhibitor, in relapsed and refractory follicular lymphoma (CITADEL-203): a phase 2 study - Trněný, Marek; Avigdor, Abraham; McKinney, Matthew S; Paneesha, Shankara; Wahlin, Björn E; Hrom, John S; Cunningham, David; Morley, Nicholas; Canales, Miguel; Bastos-Oreiro, Mariana; Belada, David; Devizzi, Liliana; et al. (EClinicalMedicine, 2023)
BACKGROUND: Parsaclisib, a potent and highly selective PI3Kδ inhibitor, has shown clinical benefit in patients with relapsed or refractory (R/R) B-cell malignancies. This phase 2 study (CITADEL-203; NCT03126019, EudraCT 2017-001624-22) assessed efficacy and safety of parsaclisib monotherapy in patients with R/R follicular lymphoma (FL). METHODS: Patients ≥18 years of age with histologically confirmed R/R FL (grade 1-3a) and prior treatment with ≥2 systemic therapies received parsaclisib 20 mg once daily (QD) for 8 weeks then parsaclisib 20 mg once weekly (weekly dosing group [WG]) or parsaclisib 20 mg QD for 8 weeks then parsaclisib 2.5 mg QD (daily dosing group [DG]); DG was selected for further assessment. Primary endpoint was objective response rate (ORR). FINDINGS: At data cut-off (January 15, 2021), 126 patients had been treated (WG: n = 23; DG: n = 103). ORR (95% confidence interval [CI]) was 77.7% (68.4-85.3) with a complete response rate (95% CI) of 19.4% (12.3-28.4) in DG; median (95% CI) duration of response was 14.7 months (10.4-not estimable [NE]), median progression-free survival was 15.8 months (11.0-NE), and median overall survival was not reached. The most common any-grade treatment-emergent adverse events (TEAEs) among all treated patients included diarrhoea (n = 48, 38.1%), nausea (n = 31, 24.6%), and cough (n = 28, 22.2%); the most common grade ≥3 TEAEs were diarrhoea (n = 15, 11.9%), neutropenia (n = 13, 10.3%), and colitis (n = 7, 5.6%). Dose interruption, reduction, and discontinuation from TEAEs occurred in 46.8% (n = 59), 17.5% (n = 22), and 23.8% (n = 30) of patients, respectively. INTERPRETATION: Treatment with parsaclisib demonstrated rapid and durable responses, and a manageable safety profile in patients with R/R FL. FUNDING: Incyte Corporation.
Keywords: PI3K inhibitor; Follicular lymphoma; Non-Hodgkin lymphoma; Parsaclisib